HUKUM PERBUATAN ROASTING DALAM STAND UP COMEDY DITINJAU BERDASARKAN KETENTUAN SYARI'AT ISLAM - Mustafid Mustafid (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
Jokes are entertaining for people who have a lot of fans in Indonesia, including single jokes or often known as Stand Up Comedy.Stand Up Comedy has terms in it, one of which is Roasting.Roasting is a mockery / made by a comedian to the object being roasted.In this paper, I want to examine how the Roasting law in Stand Up Comedy is reviewed based on the production of Islamic Shariah.This research is a normal research with a qualitative approach, while the type of research is descriptive analytical.The results of this study are that jokes in Islam are not something new and are not rejected by Islam.Of course the joke must be in accordance with Islamic ShariahThen the Roasted Muslims in Stand Up Comedy which contains elements of making fun, mocking, a person or a group is prohibited in Islam and the act of Roasting.